LITERATURE REVIEW: STRESS AND STRESS COPING STRATEGIES DURING ONLINE LEARNING - Byong Muhammad Rashadri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The Covid-19 pandemic presents new obstacles and challenges for the world, especially in the field of education. The new policy of the Indonesian government in the Circular of the Minister of Education and Culture Number 36962/MPK.A/HK/2020 explains and emphasizes that every teaching and learning process in schools and campuses in every university uses online or online learning methods. However, the learning method that has been changed to online makes it difficult for students to attend lectures. This causes anxiety and stress in students. Therefore, students need to do stress coping strategies, namely efforts to manage stress. The purpose of this study is to collect research articles that describe coping with stress in students who conduct online lectures during the pandemic and to find out whether stress coping strategies for students in online lectures can reduce stress. The approach or type of literature review used by researchers is scoping review. The database used includes Google Scholar based on keywords. The results obtained from 10 research articles reviewed can be seen that there is a relationship between coping mechanisms and stress levels during distance lectures. Not a few students experience stress due to the online lecture system that is applied. Thus, appropriate stress coping behavior is needed so that stress is handled properly. Conclusions There are two coping strategies that are quite effective in dealing with stress due to distance learning, including emotional focus coping and problem focus coping.